Exploring gay men's experiences of intimate partner violence - Echeverria, Nur Eldeen Musa (Animo Repository, 2012)
The increasing incidence of intimate partner violence has emerged as a pressing public health issue today. While there were studies conducted on this subject both locally and internationally, majority of them were focused on women who have been victims of this phenomenon. Moreover, there were hardly any empirical data on the experiences of men, most especially homosexual men who were victims of partner violence in same-sex intimate partnership. To respond to this gap, this study was conducted among 15 homosexual men who have recently experienced intimate partner violence in Zamboanga City, Philippines. The gay men were selected through a non-probability purposive and snowball sampling, and qualitative in-depth interview guide was used to investigate their personal characteristics, their abusive partners characteristics, the gender roles they assumed as intimate partners, the forms of intimate partner violence they recently experienced, and their health-related consequences. The findings revealed that violence is prevalent among intimate partners who both easily got jealous of their partners activities outside their relationship. Additionally, intimate partner who attributed women-associated traits such as being a nagger, socially active and subservient were subjected to intimate partner violence. Moreover, feminine gender roles portrayed by the key informants were found to have a bearing on the occurrence of abuse. The findings also showed that psychological abuse, more specifically verbal and emotional abuse was the most common form of IPV reported by the abused partners in this study. The health-related consequences brought about by IPV that were most mentioned by the abused partners were also psychological. Homosexual men who assumed gender roles and exhibited characteristics associated with women are more likely experience intimate partner violence. This entails that the local government units specifically the city health offices, city social welfare offices and other gender-based organization are well equipped in addressing this issue not just among women or men in heterosexual relationship but among lesbian, gay, bisexual and transgender community as well.